2021
DOI: 10.1136/neurintsurg-2021-017970
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of endovascular coiling and neurosurgical clipping for aneurysmal subarachnoid hemorrhage in Thailand

Abstract: BackgroundFor patients with aneurysmal subarachnoid hemorrhage (aSAH), the Universal Coverage Scheme in Thailand covers the full costs of surgical and endovascular procedures except for those of embolization coils and assisting devices. Costs and effectiveness were compared between endovascular coiling and neurosurgical clipping to inform reimbursement policy decisions.MethodsCosts and quality-adjusted life years (QALYs) were compared between coiling and clipping using the decision tree and Markov models. Mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…15 An acute stroke care quality improvement program with hospital bypass to reduce intravenous thrombolysis treatment delays was found to be feasible and effective in China, 16 and a regional study in Canada determined that hospital bypass was more cost-effective than using transfer protocols. 17 Treatment models independent of transport protocols that leveraged endovascular therapy in Thailand 18,19 and Greece 20 were determined to be cost-effective. Healthcare insurance coverage was recommended to reduce inequities in evidence-based care, in-hospital mortality and costs in Iran and China.…”
Section: Research To Inform Policy Redesignmentioning
confidence: 99%
“…15 An acute stroke care quality improvement program with hospital bypass to reduce intravenous thrombolysis treatment delays was found to be feasible and effective in China, 16 and a regional study in Canada determined that hospital bypass was more cost-effective than using transfer protocols. 17 Treatment models independent of transport protocols that leveraged endovascular therapy in Thailand 18,19 and Greece 20 were determined to be cost-effective. Healthcare insurance coverage was recommended to reduce inequities in evidence-based care, in-hospital mortality and costs in Iran and China.…”
Section: Research To Inform Policy Redesignmentioning
confidence: 99%
“…By contrast, a recent study from Thailand has reported a cost-effectiveness analysis of endovascular coiling and neurosurgical clipping for aSAH and revealed that endovascular treatment for aSAH is cost-effective based on their national health insurance programs. 2 I greatly appreciate the effort of the authors in performing this study. However, there are certain limitations to this study that must be acknowledged.…”
mentioning
confidence: 95%